Customers becoming creators: how firms leverage technology and consumers for new value. Issue 4 (27th July 2018) - Dal Zotto, Pierre; Colombero, Sylvain; Pigni, Federico; Haggège, Meyer
Abstract : Purpose: The rapid development of information and communication technologies (ICTs) has facilitated consumers' involvement in firms' value creation processes through increasingly near real-time information exchanges. This strategic opportunity configures new forms of ICT-enabled collaboration between firms and consumers. Firms can now immediately react to consumers' requests/complaints, having gained real-time visibility of consumers' actions and behaviors. Despite the increasing deployment of ICT-enabled value co-creation projects, managers still poorly apprehend them as high-potential strategic initiatives. Design/methodology/approach: This paper investigates this gap through a multiple qualitative case study based on 17 organizations that successfully implement ICT-based value co-creation initiatives, including Lego, Netflix and Blablacar. Findings: This study identifies two dimensions of the ICTs' value co-creation process, namely, the firms' involvement and customers' role, in this co-creation process. Through these dimensions, four ICT-based co-creation initiatives are observed and defined: community, customers' contributions create the firms' value proposition (FVP); customization, customers' service consumption personalize FVP; reputation, customers' contributions about the offered services completes the FVP; and sense, an algorithmic approach, designed to focus on learning from customers' consumption tailors FVP. Originality/value: This study advances a framework supporting managerial decision-making concerning the aptitude of co-creation initiatives to meet organizational goals. Managers may gain insight from its use especially in assessing emerging opportunities to engage consumers in the value creation process.